Hunted hotel by Ron Roy; illustrated by John Steven Gurney - Roy, Ron; Gurney, John, ill. (New York Random House, 1999)
When the guests of the Shangri-la Hotel are scared away by a white-haired female ghost, Dink and his friends investigate the mystery.
A Stepping Stone book.
Keywords: Ghosts-Fiction; Hotels, motels, etc.-Fiction; Mystery and detective stories